Analysis of lymphocytic leukemia trends among gender, race, age, and regional groups in the U.S. between 1999-2022: a CDC-WONDER database study - Blee, Shannon; Weng, Bob; Billion, Taylor; Jabbar, Ali Bin Abdul; Tauseef, Abubakar; Mirza, Mohsin (Frontiers in Oncology, 2025)
BackgroundLymphocytic leukemia (LL) is a prominent group of hematological cancers afflicting both children and adults of all backgrounds and demographics. While treatment is improving, the confounding variables on mortality and prevalence within the patient population are poorly understood. This study utilizes the Center for Disease Control and Prevention (CDC)-WONDER database to further elucidate age-adjusted mortality rates (AAMRs) in the U.S. from 1999-2022.MethodsMortality data was obtained from the CDC-WONDER database from 1999-2022. AAMRs and trends by gender, race, region, state, urban vs. rural, and age were analyzed using a Joinpoint analysis program to calculate average annual percentage change. Statistical significance was set at p ≤0.05.ResultsBetween 1999 and 2022, there was a decrease in overall mortality rates up until 2018, followed by an increase from 2018 to 2022. Men experienced higher age-adjusted mortality rates (AAMRs) than women, though women saw a greater decrease in mortality. Patients aged 85 and older had the highest crude mortality rates from 1999 to 2019. From 2019 to 2022, the White patients/White population had the highest AAMRs, while the American Indian/Alaska Native population experienced the largest increase in mortality between 2016 and 2022. Regionally, the Midwest and West consistently had higher AAMRs compared to other regions, with the Midwest having the highest AAMR and the smallest decline in mortality. From 1999 to 2019, Iowa saw the largest increase in AAMRs, while Kansas experienced the largest increase from 2019 to 2022. Rural areas consistently had higher AAMRs than urban areas throughout the period from 1999 to 2022, with both regions showing a decline in AAMRs starting in 2020.ConclusionLL overall mortality decreased from 1999–2022 but varied significantly amongst demographic groups. The Midwest, rural, older, and non-Hispanic white populations experienced the largest mortality rates. Thus, policies and management plans should be developed accordingly to these biases in disparities.